2003
DOI: 10.1097/00002030-200311210-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-specific IFN-γ production is associated with protection against cytomegalovirus reactivation in HIV-infected patients on highly active antiretroviral therapy

Abstract: Cytomegalovirus-specific IFN-gamma has a unique value as an immunological predictor of cytomegalovirus reactivation, demonstrating the importance of cellular immune responses in the control of cytomegalovirus replication in HAART recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…CMV lysate-stimulated IFN-␥ production had the highest HIV RNA discriminative threshold of approximately 5,000 to 10,000 copies/ml plasma. This threshold is similar to the benchmark of 10,000 HIV RNA copies/ml associated with the increased incidence of CMV end-organ disease (8) and is also in agreement with a previously reported association between the CMV-specific IFN-␥ responses and protection against CMV end-organ disease (27,34,36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CMV lysate-stimulated IFN-␥ production had the highest HIV RNA discriminative threshold of approximately 5,000 to 10,000 copies/ml plasma. This threshold is similar to the benchmark of 10,000 HIV RNA copies/ml associated with the increased incidence of CMV end-organ disease (8) and is also in agreement with a previously reported association between the CMV-specific IFN-␥ responses and protection against CMV end-organ disease (27,34,36).…”
Section: Discussionsupporting
confidence: 91%
“…IFN-␥ assays specific for other microbial agents, such as Mycobacterium tuberculosis, are commercially available for investigation of pathogen-specific CMI. A standardized CMV-specific IFN-␥ assay may also find clinical utility, considering that several studies have shown an association between the CMV-specific IFN-␥ production and protection against CMV end-organ disease not only in HIVinfected individuals but also in transplant recipients and other immunocompromised hosts (27,29,34,36).…”
Section: Discussionmentioning
confidence: 99%
“…Most PBMC cultures from all but four patients were seen to secrete IFN-g (but not IL-4) upon HCMV stimulation, even at normal levels. Comparable results have been reported previously by Weinberg et al [2001] and by several investigators [Waldrop et al, 1997;Keane et al, 2000;Komanduri et al, 2001;Piccinini et al, 2001;Grosse et al, 2002;Alfonzo et al, 2003;Weinberg et al, 2003] who instead used cell cytometry to measure IFN-g producing HCMV-specific CD4 þ T cells. No significant association was found between pre-HAART nadir CD4 þ T cell levels and reconstitution of the IFN-g response, yet patients who failed to recover such a response had very low nadir counts.…”
Section: Discussionsupporting
confidence: 83%
“…Studies of profoundly immunocompromised patients with advanced HIV disease or undergoing bone marrow transplantation have reported that absence of CMV-specific CD4 + T cells that express IFN-γ or proliferate in response to in vitro CMV stimulation and absence of CMV-specific CTL responses are each associated with increased risk of developing CMV end organ disease (5)(6)(7)(8). Reduced HIV-specific CD8 + T cell proliferation responses have been associated with HIV progression [17], but the ability of CD8 + T cells to proliferate in response to ex vivo CMV antigen stimulation has not been examined in the context of clinical CMV immune protection.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory correlates of this immune protection in healthy CMV seropositive individuals are not fully understood. Although previous studies have suggested that viral-specific CD4 + and CD8 + T cell cytokine expression and proliferation responses are each important in immune protection for CMV disease as well as disease caused by other chronic viral infections (2,(5)(6)(7)(8)(9), there have been no studies that have examined both types of CMV-specific responses for both CD4 + and CD8 + T cells in the same group of healthy CMV-seropositive individuals. A more complete characterization of the immune response to CMV in normal healthy seropositive individuals could help to define what is lacking in the immune responses of patients with CMV end organ disease.…”
Section: Introductionmentioning
confidence: 99%